Antibiotic Stewardship and Hospital Hygiene in German Paediatric Inpatient Facilities: A Qualitative Survey from the Paed IC Working Group - Weiss, K.; Simon, A. (Klinische Pädiatrie, 2016)
Background: Antibiotic stewardship (ABS) and hospital hygiene have both been identified as key components to increase patient safety in hospital inpatients. To set the stage for a new approach in this field, a working group of German Pediatric Infectious Disease (PID) Specialists invented the Paed IC Project in 2012.Methods: This article summarized the results of a qualitative study using telephone interviews, to which 18 German PID specialists were invited.Results: All local study coordinators and additional PID specialists from the 11 paediatric tertiary care inpatient facilities consented to participate. Only 3 of 18 participants (16.7%) are medical directors of an independent PID department. The majority of the participants agreed with the statement, that there is a need for a national clinical practice guideline (in Germany) which outlines specific paediatric aspects of ABS. In addition, concise internal clinical practice guidelines describing the most important PIDs in addition to the Handbook “Infections in Children and Adolescents” published by the DGPI were deemed necessary. 89% denied having access to any financial reimbursement allocated to cover systematic clinical audits. The hospital administration in most participating hospitals (72%) does not provide the medical specialties with personnel/financial resources to implement an ABS-program as recommended by recent guidelines.Conclusion: This qualitative study adds important information to adjust future strategies for ABS implementation in German paediatric inpatient care facilities.
Keywords: antibiotic stewardship; paediatrics; qualitative study; antibiotic resistance; paediatric infectious diseases